2008
DOI: 10.1213/ane.0b013e318160650f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitochondrial Large-Conductance Calcium-Activated K+ Channels via Protein Kinase A Mediates Desflurane-Induced Preconditioning

Abstract: These data suggest that desflurane-induced APC is mediated in part by activation of mitochondrial large-conductance K(Ca) channels, and that activation of these channels by desflurane is mediated by PKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 40 publications
7
54
0
2
Order By: Relevance
“…Concluding from other studies on the same experimental model, 21,23,28 we expected a myocardial IS of 50% (IS/AAR). Power analysis revealed a group size of n = 8 to detect a reduction in means of 15% with a power of 0.8 at a a-level of 0.05.…”
Section: Data Acquisition and Statistical Analysissupporting
confidence: 65%
“…Concluding from other studies on the same experimental model, 21,23,28 we expected a myocardial IS of 50% (IS/AAR). Power analysis revealed a group size of n = 8 to detect a reduction in means of 15% with a power of 0.8 at a a-level of 0.05.…”
Section: Data Acquisition and Statistical Analysissupporting
confidence: 65%
“…In fact, cytoprotection by mK Ca channel activation is supported by the findings that a activator (NS1619) and blockers (charybdotoxin, paxilline) of the Ca 2+ -activated K + channel in the cell membrane (K Ca + channel) were effective in manipulation of the mK Ca channel in mitochondria [74,75], that K Ca channel openers limited infarct size and that blockers of the K Ca channel (paxilline, iberiotoxin, charybdotoxin) or knockdown of the β1 subunit of the K Ca + channel inhibited infarct size-limiting effects of adrenomedulin [75], desflurane [76], sildenafil, [77] and IPC [78]. Furthermore, transient activation of the mK Ca channel by NS1619, like that of the mK ATP channel, has been shown to increase ROS production, leading to transmission of cytoprotective signaling [79,80].…”
Section: Cytoprotective K + Channels In Mitochondriamentioning
confidence: 99%
“…Modern volatile anaesthetics as elicitors of cardiac preconditioning have been effectively demonstrated in cell culture experiments [1,2] and animal models [3,4,5,6]. There is also supporting evidence from clinical studies that anaesthetic-induced preconditioning (APC) is protective in the clinical setting [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent molecular investigations of DES-PC were conducted with focus on specific targets known from IPC [2,3,4,5,11,12] but the overall picture of the underlying mechanisms is still lacking. A couple of studies even showed that the signalling pathways may differ from IPC [6,13].…”
Section: Introductionmentioning
confidence: 99%